Malaysian model of work-family interface : Similar or different from the West? - Zaiton, Hassan; Maureen F., Dollard; Anthony H., Winefield (Springer Netherlands, 2014)
Currently, work-family interface (WFI) research is primarily based on data from Anglo samples within Western developed countries. Little is known about WFI in Eastern developing countries. This raises the question of how well the Western model of WFI could be generalized to other cultures. Therefore this research study aims to highlight the work-family interface model in Malaysia, a predominantly collectivist society with Islam as the official religion. Resources and demands from the work and family domains and from the community domain are investigated. Similar to Western findings, resources were significantly and positively related to work-family enrichment, while demands were significantly and positively related to work-family conflict. However, in contrast to Western results, resources and demands from community domains made a more significant contribution to work-family conflict and enrichment as compared to resources and demands from the work and family domains. Cultural dimension namely, polychronic time orientation, traditional gender role ideology, and religion can explain these observed differences. These findings suggest that some aspects of Western-based WFI models can be applied to Malaysia. However, the study demonstrates that the role of community and religion, which are neglected within Western WFI research, are important in determining work-family interface in Malaysia. Thus, it may be concluded that in order to have a better understanding of work-family interface in a society which is predominantly collectivist and has strong cultural beliefs and values, aspects of community and religion must be integrated.